Axiological approach to the psychological and pedagogical training of future teachers of the new generation - Kryvylova, Olena; Sosnickaya, Natalya; Сосницька, Наталя Леонідівна; Сосницкая, Наталья Леонидовна; Oleksenko, Karina (My University, 2020)
The role of axiological approach in the training of new generation teachers is theoretically substantiated in this article. The axiological approach makes it possible to identify a set of priority values in the education, upbringing and self development of a person in modern society and to design their reflection in the norms and aims of future teachers in the process of psychological and pedagogical training. Possible ways of implementing an axiological approach in the educational process of higher education institutions are outlined, such as: the identification of value orientations of higher education applicants, with further adjustment regarding ethical positions in psychological and pedagogical activity; informing students of higher education about value orientations and identification of the most important ones in teaching the cycle of psychological and pedagogical disciplines; adaptation of higher education students to the system of professional value orientations through educational, practically-oriented, independent activity and interaction with teachers as carriers of moral principles and others. Thus, 45.83% of respondents found: having ethical knowledge about generally accepted norms and principles of pedagogical morality; mastering the basic requirements of pedagogical ethics; ability to act positively according to moral choice; the need to work independently to improve themselves and improve their moral qualities.
Keywords: axiological approach; ethical values; psychological and pedagogical training; new generation teacher